Novel Approaches to Diagnose COVID-19 - Ali, Solaf Jawhar (Kurdistan Journal of Applied Research, 2020)
An widespread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in December 2019 has occurred worldwide. Public health agencies are in need of developing diagnostic tools which will have a major impact in tracking the virus and suppressing the transmission. Diagnosis of the disease is based on clinical symptoms, epidemiological history and laboratory examinations. Severe acute respiratory diseases with fever and ,cough and dyspnea, are used as the case definition to select people for testing. Different samples taken from the human body such as oropharyngeal (OP) and nasopharyngeal (NP) swabs are used to detect the virus. SARS-CoV-2 can be detected with different methods in the laboratory including real time RT-PCR, chest CT scan and immunoassays. Viral nucleic acid testing has played important role in control COVIDI-19 outbreak. More recently, a new CRISPR-based DETECTR assay has been developed to detect COVID-19. This test is rapid ( 30 min), low-cost, and precise for identification of SARS-CoV-2. In addition, immunoassays and medical imaging can use as supplementary tests, combined with RT-PCR. This review is conducted to summarizes the current information on the present diagnostic approaches for SARS-CoV-2.